CLINICAL PSYCHOLOGY AND PSYCHIATRY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article is aimed at analyzing the interrelationships, differences, and integrative approaches in the fields of clinical psychology and psychiatry. The introduction discusses the historical development of clinical psychology and psychiatry, their importance in the modern healthcare system, and their role in the diagnosis and treatment of diseases. The methods section compares and analyzes the diagnostic tools (for example, DSM-5, ICD-11), psychotherapy methods, and pharmacological approaches used by representatives of both fields. The results showed that clinical psychologists focus primarily on helping patients through psychotherapy, cognitive-behavioral therapy, and psychodiagnostics, while psychiatrists focus on understanding diseases from a neurobiological perspective and treating them with medications. The possibilities of improving patient well-being through multidisciplinary teamwork were also highlighted.